Parental involvement in their adolescents' organized youth programs: Perspectives from parent-adolescent dyads. Issue 1 (2nd January 2022) - Munoz, Lorraine; Raffaelli, Marcela
Abstract: The current study explored how parents and their adolescent children describe parents' involvement in the adolescent's organized youth program. As part of a larger study of youth programs, 36 adolescent-parent dyads participated in semi-structured interviews. Youth (63.9% female) were 13–18 years old ( M  = 15.9, SD  = 1.2) and ethnically diverse (38.9% Latino/a, 36.1% European American, and 25% African American or Black). Qualitative analyses centered on two domains of parental involvement ( type and level ). Parents and adolescents focused on different types of involvement, with parents most commonly describing on-site involvement in their children's programs (e.g., attending activities, volunteering) and adolescents emphasizing parents' off-site involvement (e.g., emotional or informational support). Despite these differences, most respondents described the level of parental involvement as "good." Factors that inhibited parents' involvement in their child's program activities were also identified (primarily competing obligations or work conflicts). Implications for research and practice are discussed.